A Novel ZNF304/miR-183-5p/FOXO4 Pathway Regulates Cell Proliferation in Clear Cell Renal Carcinoma - Ren, Li-Xin; Zeng, Bo-Wen; Zhu, Meng; Zhao, An-Ning; Shi, Bei; Zhang, Hong; Wang, Dan-Dan; Gu, Jun-Fei; Yang, Zhan (Frontiers in Oncology, 2021)
Zinc-finger protein 304 (ZNF304) plays a critical role in silencing genes through transcription, regulating cell survival, proliferation, apoptosis, and differentiation during development. However, the roles of transcription factor ZNF304 and its clinical significance in clear cell renal carcinoma (ccRCC) remain unclear. In this study, we found that the expression of ZNF304 was downregulated in ccRCC tissues. Lower levels of ZNF304 were correlated with poor survival. Downregulation of ZNF304 promoted ccRCC cell growth in vitro, whereas overexpression of ZNF304 inhibited growth. Our results indicated that miR-183-5p/FOXO4 mediated ZNF304 regulation of cell growth. Interestingly, we revealed that ZNF304 promoted FOXO4 expression in ccRCC cells. Mechanistically, ZNF304 binds to miR-183 promoter and inhibits miR-183-5p transcription. Furthermore, the expression of miR-183-5p wes increased in ccRCC tissues, and the upregulation of miR-183-5p was related to the poor prognosis of ccRCC patients. miR-183-5p upregulation repressed the expression of FOXO4 and promoted ccRCC progression. These results demonstrated that ZNF304/miR-183-5p/FOXO4 axis played essential role in promoting ccRCC progression, which suggests that disruption of this axis may be a potential therapeutic target in ccRCC.